Prophetic educational methods in addressing some manifestations of bullying among students as recognized by middle school teachers - Al-Essi, Ahmed Mohammed (Journal of Educational and Psychological Sciences, 2023)
This study aimed to reveal the prophetic educational methods in addressing some manifestations of bullying among students according to variables: professional experience in education, training courses, and to achieve this goal, the study relied on the descriptive survey methodology, appropriate to the nature of the study, and the study community consisted of the public middle school’s teachers at Jeddah, a total of 5276 teachers, and a random sample of (358) teachers were selected, and the researcher took the questionnaire as a study tool. The results indicate that the level of pedagogical methods used by teachers to deal with bullying among middle school students is generally high. The most prophetic educational methods that confront bullying among students are those related to the method of good preaching, exploitation the life situations, forbidding, and education by example, while the least prophetic educational methods that confront bullying among students are those related to the method of deprivation, intimidation, gradualism, and persuasion. The results also indicated the effectiveness of teacher training in reducing bullying. And that experienced professional teachers are more effective in using life situations to benefit students by promoting positive behavior and correcting negative behavior. In light of these results, the study suggested establishing educational and extension programs to help students reduce bullying and familiarize them with the risks of bullying, in addition to providing the necessary support for experienced teachers to benefit from the best educational methods and techniques to deal with bullying.